Istiḥālah and Ḍarūrah Theory Approach to the Law on the Use of Vaccines for Astrazeneca Products - Abdul Wahid Haddade; Khaerul Anam; Khaerul Anwar (MUI Sulawesi Selatan, 2022)
This study aims to describe and analyze the legal review of istiḥālah and ḍarūrah on the Indonesian Ulema Council Fatwa Number 14 of 2021 concerning the use of the AstraZeneca vaccine. A library study was conducted on some literature using a qualitative descriptive approach. The results showed that the limited supply of vaccines hindered the success of vaccination. Furthermore, the insufficient availability of the lawful and holy Covid-19 vaccine was also a problem encountered, hence the Fatwa Commission of the Indonesian Ulema Council (MUI) issued fatwa Number 14 of 2021. The Central MUI decision allowed the use of the AstraZeneca vaccine based on emergency conditions. They used the rules of istiḥālah and istiḥlāk narrowly and were not enforced because the Astrazeneca vaccine was not made from pork but used pork-derived ingredients. Furthermore, the fatwa was determined using the istinbāţ rules used as guidelines, which included three methods, namely, the bayānī, ta’līlī, and istilahsi. The adopted methodology in issuing this fatwa was the istişlaḥī method or maşlaḥah mursalah. Regarding the Astrazenecase vaccine, the final decision was the same and allowed. However, according to the Central MUI, the permissibility of the Astrazeneca vaccine was an emergency.